Development and evaluation of an educational intervention in youth mental health for primary care practitioners. (22nd December 2014) - Birrane, J.; Swan, D.; Aherne, D.; Davis, R.; Hannigan, A.; McPhillips, D.; Meagher, D.; O'Regan, A.; Ryan, P.; Schaffalitzky, E.; Cullen, W.
Abstract : Objectives: Irish adolescents have one of the highest rates of suicide and self-harm in the European Union. Although primary care has been identified as an opportune environment in which to detect and treat mental health problems in adolescents, lack of training among primary care professionals (PCPs) is a barrier to optimum identification and treatment. We describe the development and evaluation of an educational intervention on youth mental health and substance misuse for PCPs. Methods: Thirty general practitioners and other PCPs working in the Mid-West region participated in an educational session on youth-friendly consultations, and identification and treatment of mental ill-health and substance use. Learning objectives were addressed through a presentation, video demonstration, small group discussions, role play, question-and-answer sessions with clinical experts, and an information pack. Following the session, participants completed an evaluation form assessing knowledge gain and usefulness of different components of the session. Results: A total of 71% of participants were involved in the provision of care to young people and 55% had no previous training in youth mental health or substance abuse. Participants rated knowledge gains as highest with regard to understanding the importance of early intervention, and primary care, in youth mental health. The components rated as most useful were case studies/small group discussion, the 'question-and-answer session' with clinical experts, and peer interaction. Conclusions: The educational session outlined in this pilot was feasible and acceptable and may represent an effective way to train professionals to help tackle the current crisis in youth mental health.